Diversity and distribution of mollusks in mangrove ecosystem of University of Eastern Philippines, Catarman, Northern Samar - Balanquit, Krizza Angela S. (2022)
Mangrove ecosystems are transitional coastal formations between the terrestrial and aquatic ecosystems. These ecosystems provide a broad range of niches for many vertebrates and invertebrates that are commonly found in terrestrial and aquatic habitats. Mollusks are one of the dominant invertebrate faunal components in the mangrove ecosystems. In mangrove ecosystems, mollusks can be found colonizing a variety of habitats and they are known to exhibit a great ecological role to these environments. The study reported in this paper sought to analyze the composition, diversity and abundance of mollusk species in the mangrove ecosystem of UEP, Catarman, Northern Samar and relate this to selected biophysical factors, specifically vegetation cover and environmental parameters. Data collection used transect line plot method (plot size 10 x 10 meters square) with 1 x 1 meter square quadrats laid in certain intervals. This research found 49 species of mollusks belonging to class Gastropoda and class Bivalvia. Most of the identified and classified species are gastropods represented by 41 species belonging to 29 genera of 18 families, while bivalves accounts for the rest with 8 genera of 5 families. Despite the low mangrove density, the diversity and evenness of molluscan species within the research station is in good condition. This can be attributed to the overall condition of the environmental parameters within the area which provides a stable and suitable habitat for mollusks to survive and to settle.